Experimental investigation of the effect of silica fume on the thermal spalling of reactive powder concrete. (30th November 2017) - Ju, Yang; Tian, Kaipei; Liu, Hongbin; Reinhardt, Hans-Wolf; Wang, Li
Highlights: The effects of silica fume (SF) on the thermal spalling of RPC were investigated. The RPC achieved the largest compressive strength with 16% SF replacement. The RPC presented the best high-temperature resistance with 8% SF replacement. Microstructural phases of C-S-H gels and the mechanical properties were analysed. A conceptual model was used to interpret the effect of SF on RPC's spalling. Abstract: The distinct spalling performances of reactive powder concrete (RPC) specimens with various silica fume (SF) contents exposed to high temperatures were observed via high-resolution photography. The RPC microstructures and pore structures after high-temperature exposure were characterized using scanning electron microscopy and mercury intrusion porosimetry. The results provide experimental evidence of the high-temperature spalling mechanism of RPC. Increasing the SF content in RPC increases its compressive strength and compactness, offering greater mitigation of devastating spalling behaviour, but also producing more pulverized spalling remnants. This is attributed to the post-heating cracked microstructure and refined pores, which promote localized rather than entirely explosive spalling.